The Influence of the SCL Method on Enhancing Students’ Independence in English learning - Sulistiyaningsih, Riski; Nur Fadhilah (English Language and Education Spectrum, 2025)
English as a foreign language is a compulsory subject in every study program at university. English given in non-English departments is usually called English for specific purposes (ESP). Therefore, the English material given is adjusted to each department. However, in non-English departments, students sometimes feel bored in attending English learning process because it is not their interest. Lecturers must provide material without making students bored and make fun learning atmosphere so that students are active during the learning process. This research discusses the influence of student-centered learning (SCL) in English learning process, especially in non-English department students, related to the students' learning independence. This research uses a qualitative descriptive method using observation. The study used a sample of 38 non-English department students who took English course in one semester as respondents. Data were obtained from observations in learning process, questionnaires, and English score obtained by the students. Data analyses using percentage of questionare result and the mean score of the students as additional evidence of research result. The research results show that almost 90% students being active in the English class using SCL if the material related to their major. If the material is about English grammar which explained using SCL through students’ presentation, they are still difficult to understand the material. Grammar material is easier for students to understand if it is explained by the lecturer or what is called teacher-centered learning (TCL). In other words, lecturers can apply SCL in the English learning process for materials related to each major (ESP) to increase students’ activeness and independence during the learning process.